Research Trend of Citizen Science Themes 2019-2024: Systematic Literature Review - Ilhami, Aldeva; Hidayat, Topik; Riandi, Riandi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Citizen Science has emerged as a popular and widely used approach in scientific research. This study analyses CS research through the lens of themes, research locations, and data analysis methods. A systematic literature review employing the PRISMA method was conducted, resulting in the analysis of 45 relevant articles retrieved from the Science Direct database. The results indicate that environmental pollution (31%) and conservation (24%) were the most prevalent project topics within CS research. Questionnaires emerged as the dominant data collection technique, while quantitative analysis methods were more frequently employed. Furthermore, the geographical distribution of CS research revealed a concentration in America and Europe. Notably, the application of CS research remains limited in Asia and Africa. An additional finding suggests a gap in research focusing on educational themes, particularly those exploring the involvement of educatorstudents, a local traditional leader in Citizen Science ProjectKeywords: citizen science; research trends; systematic literature review